When Gendered Logics Collide: Going Public and Restructuring in a High-Tech Organization. Issue 4 (August 2019) - Mickey, Ethel L.
Gender scholars argued that gendered organizations theory needs updating as organizational logic has shifted amid neoliberal workplace transformations. This qualitative case study of a high-tech firm reveals how features of the traditional work logic remain resilient. I analyze the gendered implications of a high-tech startup restructuring and going public, finding the flexible organization to bureaucratize, implementing specialized jobs and a hierarchy with standardized career ladders. Going public creates conflicting gendered logics that place women at a structural disadvantage, relegating them to low-status, narrow jobs while simultaneously demanding masculine ideal worker norms of visibility and self-promotion. Despite networking, women experience job insecurity and a glass ceiling, while men are assumed ideal workers and advance. By tracing one high-tech firm's restructuring from a startup to public company, I demonstrate how the collision of new and traditional workplace logics perpetuates gender inequalities.